Semi-automatic modeling of buildings from digital surface models - dos Santos, Daniel R.; Tommaselli, Antonio M.G. [UNESP]; Dalmolin, Quintino (Taylor & Francis, 2004)
Semi-automatic building detection and extraction is a topic of growing interest due to its potential application in such areas as cadastral information systems, cartographic revision, and GIS. One of the existing strategies for building extraction is to use a digital surface model (DSM) represented by a cloud of known points on a visible surface, and comprising features such as trees or buildings. Conventional surface modeling using stereo-matching techniques has its drawbacks, the most obvious being the effect of building height on perspective, shadows, and occlusions. The laser scanner, a recently developed technological tool, can collect accurate DSMs with high spatial frequency. This paper presents a methodology for semi-automatic modeling of buildings which combines a region-growing algorithm with line-detection methods applied over the DSM.
Keywords: Building modeling; Laser scanner; Laser scanner image; Semi-automatic extraction; Geographic information systems; Laser applications; Mapping; Scanning; Building detection; Building extraction; Digital surface model (DSM); Stereo matching techniques; Buildings; building; digital map; laser; modeling